Photoactivated Artificial Molecular Machines that Can Perform Tasks. Issue 20 (20th January 2020) - Corra, Stefano; Curcio, Massimiliano; Baroncini, Massimo; Silvi, Serena; Credi, Alberto
Abstract: Research on artificial photoactivated molecular machines has moved in recent years from a basic scientific endeavor toward a more applicative effort. Nowadays, the prospect of reproducing the operation of natural nanomachines with artificial counterparts is no longer a dream but a concrete possibility. The progress toward the construction of molecular‐machine‐based devices and materials in which light irradiation results in the execution of a task as a result of nanoscale movements is illustrated here. After a brief description of a few basic types of photoactivated molecular machines, significant examples of their exploitation to perform predetermined functions are presented. These include switchable catalysts, nanoactuators that interact with cellular membranes, transporters of small molecular cargos, and active joints capable of mechanically coupling molecular‐scale movements. Investigations aimed at harnessing the collective operation of a multitude of molecular machines organized in arrays to perform tasks at the microscale and macroscale in hard and soft materials are also reviewed. Surfaces, gels, liquid crystals, polymers, and self‐assembled nanostructures are described wherein the nanoscale movement of embedded molecular machines is amplified, allowing the realization of muscle‐like actuators, microfluidic devices, and polymeric materials for light energy transduction and storage. Abstract : Artificial molecular machines powered by light can nowadays be integrated in organized environments such that the molecular movements can be harnessed to execute a task. The resulting functional devices and materials can lead to radical innovation in catalysis, microfluidics soft robotics, medical diagnostics and therapy, and solar energy conversion.